India's Mahatma Gandhi National Rural Employment Act: Assessing the quality of access and adequacy of benefits in MGNREGS public works. (7th September 2016) - Ehmke, Ellen
Abstract: The extension of social protection to all has become a central policy objective, both nationally and internationally. A considerable number of middle‐ and low‐income countries have undertaken substantial efforts to extend social protection, while the international community reaffirmed its commitment to the extension of social protection through the adoption of the ILO Recommendation concerning National Floors of Social Protection, No. 202 (2012). This article reviews the legal provisions and the implementation of the Indian Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), legislated in 2005, and does so in the light of the more recent provisions of ILO Recommendation No. 202. Since its introduction ten years ago, MGNREGA has provided a source of income to rural workers, increased wage rates, achieved high female participation rates and created durable assets. India's local governance bodies, Panchayati Raj Institutions (PRI), have been empowered and involved in the processes of planning and monitoring. However, despite successes, there have been considerable shortcomings in implementation. This article highlights two central themes: first, the innovative policy framework of the Act, which brings together rights‐based entitlements, demand‐driven employment, and citizen‐centred monitoring. Second, it assesses the accessibility and adequacy of benefits in the implementation of MGNREGA. We conclude that MGNREGA offers potential for South‐South learning, both in terms of policy‐design and implementation.